Selection of proper activation functions in back-propagation neural networks algorithm for transformer internal fault locations - Jettanasen, Chaiyan; Pothisarn, Chaichan; Bunjongjit, Sulee; Ngaopitakkul, Atthapol; Suechoey, Boonlert (My University, 2012)
This paper presents an analysis on the selection of an appropriate activation function used in neural networks for locating the internal fault in a two-winding three-phase transformer. A decision algorithm based on a combination of Discrete Wavelet Transforms and neural networks is developed. Fault conditions of the transformer are simulated using ATP/EMTP in order to obtain current signals. The training process for the neural network and fault diagnosis decision are implemented using toolboxes on MATLAB/Simulink. Various activation functions in hidden layers and output layers are compared in order to find out and to select the best activation function for indicating the position of internal faults of the winding transformer for the winding to ground faults. It is found that the use of Hyperbolic tangent-function for the hidden layers, and Linear activation function for the output layer gives the most satisfactory accuracy in these particular case studies. © 2012 IEEE.
Keywords: Back-propagation neural network; Discrete Wavelet Transforms; Internal faults; Transformer windings